4-Acetylantroquinonol B inhibits lipopolysaccharide-induced cytokine release and alleviates sepsis through of MAPK and NFκB suppression - Chien-Hsin Chang; Chun-Chieh Hsu; An-Sheng Lee; Shih-Wei Wang; Kung-Tin Lin; Wei-Luen Chang; Hui-Chin Peng; Wen-Chiung Huang; Ching-Hu Chung (BMC, 2018)
Abstract Background Antrodia cinnamomea is an indigenous medicinal mushroom in Taiwan, commonly used for the treatment of cancers and inflammatory disorders. 4-acetylantroquinonol B (4AAQB) is one of the active component isolated from the mycelium of A. cinnamomea. However, whether 4AAQB exhibits anti-inflammatory effect is not clear. Methods The anti-inflammatory activity of 4AAQB was examined by ELISA to measure the pro-inflammatory cytokines production in lipopolysaccharide (LPS)-simulated RAW264.7 cells, peritoneal macrophages and in mice. The effect of 4AAQB for MAPK kinase molecules phosphorylation in LPS-stimulated RAW264.7 macrophage including ERK, JNK and p38 were evaluated. The in vivo efficacy of 4AAQB was also demonstrated. Results In the present study, we found that 4AAQB exhibits anti-inflammatory effects inhibit tumor necrosis factor-α (TNF-α)/interleukin-6 (IL-6) releasing and LPS-stimulated phagocytes migration without affect cell growth. In addition, the MAPK kinase molecules phosphorylation in LPS-stimulated RAW264.7 macrophage including ERK, JNK and p38 was inhibited by 4AAQB. The phosphorylation of NFκB subunit p65 and IkBα were also decreased after 4AAQB treatment. Furthermore, 4AAQB attenuates the cytokine production in LPS-induced and CLP-induced septic mice. Conclusion These results showed that 4AAQB exhibited anti-inflammatory property both in vitro and in vivo, suggesting that 4AAQB may be a therapeutic candidate which used in inflammatory disorders treatment.